Dampak Koping Religius pada Ibu yang Memiliki Anak Berkebutuhan Khusus - Hidayati, Siti Nur; Dewi, Dinar Sari Eka (PSIMPHONI, 2024)
Parents, particularly mothers of children with special needs, expressed emotions of sadness, disappointment, and resistance in coming to terms with their child's condition. This study aims to explore how religious coping influences these mothers. Employing a qualitative phenomenological approach, the researcher engaged three participants through snowball sampling. Triangulation was utilized in this research, employing semi-structured interviews and observations for data collection. Interpretative Phenomenological Analysis (IPA) using Atlas.ti 9 software was employed for data analysis. Findings revealed that participants initially experienced sadness, disappointment, fear, and unreadiness upon their child's birth. Religious coping, such as seeking solace in Allah, prayer, and spiritual practices, emerged as a crucial mechanism for navigating this challenging period. Additionally, finding meaning in their child's condition as a divine mandate and receiving social support provided participants with a sense of comfort. Participants reported that religious coping helped them find tranquility, happiness, acceptance of their child's condition, and increased patience in managing their child's behaviors.